Export response to trade liberalisation in the presence of high trade costs: Evidence for a landlocked African economy - Chris Milner; Evious Zgovu (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2003)
The paper investigates the relative importance of trade policy and 'natural' sources of export taxation in Malawi, a landlocked African economy. These sources of export taxation are in turn used to explore how export supply would respond to trade liberalisation as opposed to measures which lower other international trade costs. The findings indicate that trade policy barriers are now only a limited source of 'true' export taxation and that trade policy reform needs to be complemented with reforms to reduce international trade, including transport, costs.
Keywords: 330